Automated electronic discharge summary for patients undergoing acute scrotal exploration: does it improve accuracy and quality?. Issue 6 (December 2019) - Starmer, B.; Barton, M.; Corbett, H.
Summary: Background: The acute scrotum is a common emergency presentation, and the priority is to exclude testicular torsion, which typically requires scrotal exploration. The accuracy of electronic discharge summaries (EDSs) for patients undergoing acute scrotal exploration has previously been shown to be poor. Objective: The objective of this study was to assess accuracy of EDS in patients undergoing acute scrotal exploration in a tertiary paediatric hospital. This study aimed to determine if a new EDS system, whereby the operative procedure is automatically transcribed into the EDS, improves the information within the EDS. Methods: Retrospective review of the EDS for all patients undergoing acute scrotal exploration between 1st April 2014 and 31st March 2016 was carried out. During this period, a new EDS system, whereby the operative procedure is automatically transcribed to the EDS, was introduced on 20th June 2015. The old system (1st April 2014 to 19th June 2015) was compared with the new system (20th August 2015 to 31st March 2016). Results: A total of 181 patients were included. A diagnosis was not documented in 25 (14%) and was inconsistent with the operation notes in 56 (31%). An operative procedure was not documented at all in 13 (7%) and was inconsistent with the operation notes in 43 (24%). The laterality of pain was not documented and/or incorrect in 11 (6%). The new system in which the operative procedure is automatically transcribed to the EDS resulted in an improvement of diagnoses (78% vs 96%; p = 0.0022; old vs new) and procedures (95% vs 100%; p = 0.0218; old vs new) being documented but not the accuracy. Conclusion: The EDS prepared for patients undergoing acute scrotal exploration frequently exhibit inaccuracies; a system that automatically transcribes the operative procedure into the EDS results in modest improvement. Table 1 Quality of the EDS in the old and new system. Table 1 Aspect of EDS being assessed Old % (n) New %(n) P -value Diagnosis not documented 19 (22) 7 (4) 0.0022 Diagnosis incorrect 30 (34) 32 (17) 0.6625 Procedure not documented 5 (6) 0 (0) 0.0218 Procedure incorrect 24 (27) 10 (5) 0.349 Findings not documented 28 (32) 26 (14) 0.656 Findings incorrect 5 (6) 2 (1) 0.1687 Laterality not documented/incorrect 4 (5) 7 (4) 0.1258